The influence of reward and recognition programmes on librarian's motivation in academic libraries in Nigeia (2013)
This study highlighted " the influence of reward and recognition programs on librarian's motivation in academic libraries in Nigeria". The study was conducted from October till December;2011. The sample chosen for the study was 80 librarians selected from five academic librarians in Oyo State. The facotrs affecting librarian's motivation were identified; payment (0.86**),promotion(0.74**),working condition(0.61**),personal (0.37*) as analysis showed immense support for positive relationship between reward and librarian's motivation.All these result are statistically significant thus providing rigor and generalization in research. This exploratory study therefore suggests for the positive relationship between reward and statifaction..